2020
DOI: 10.1007/s40593-020-00193-4
|View full text |Cite
|
Sign up to set email alerts
|

Preschoolers’ Understanding of a Teachable Agent-Based Game in Early Mathematics as Reflected in their Gaze Behaviors – an Experimental Study

Abstract: This study investigated how preschool children processed and understood critical information in Magical Garden, a teachable agent-based play-&-learn game targeting early math. We analyzed 36 children's (ages 4-6 years) real-time behavior during game-use to explore whether children: (i) processed the information meant to support number sense development; (ii) showed an understanding of the teachable agent as an entity with agency. An important methodological goal was to go beyond observable behavior and shed so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 39 publications
1
19
0
1
Order By: Relevance
“…The other-gender characters were not socially meaningful in terms of gender but were socially contingent partners for children through PSIs, which support the body of work on the positive role of social contingency in children's learning from educational digital media (Barr, 2019;Calvert, 2017;Calvert et al, 2020;Kirkorian, 2018;Roseberry et al, 2014). Additionally, these results contribute to research on young children's early math learning from pedagogical agents (Gulz, Londos, et al, 2020) and support findings that peer pedagogical agents can drive learning experiences for children and facilitate the processing of on-screen content when they engage in more PSIs.…”
Section: Discussionsupporting
confidence: 60%
See 2 more Smart Citations
“…The other-gender characters were not socially meaningful in terms of gender but were socially contingent partners for children through PSIs, which support the body of work on the positive role of social contingency in children's learning from educational digital media (Barr, 2019;Calvert, 2017;Calvert et al, 2020;Kirkorian, 2018;Roseberry et al, 2014). Additionally, these results contribute to research on young children's early math learning from pedagogical agents (Gulz, Londos, et al, 2020) and support findings that peer pedagogical agents can drive learning experiences for children and facilitate the processing of on-screen content when they engage in more PSIs.…”
Section: Discussionsupporting
confidence: 60%
“…When children do not know, or do not share salient similarities with the character, like gender, it may be particularly important for characters to provide ample opportunities for a conversational back-and-forth interaction about STEM content, which has been found to support learning from peer agents (Kim & Baylor, 2006). Media characters may be effective and motivating for young children to learn math from pedagogical agents (Gulz, Kjällander, et al, 2020;Gulz, Londos, et al, 2020;Husain et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The final sample had an average tracking ratio of 47.17% with an SD of 11.97%. Considering the young age of our participants and the long durations of each of our videos (21.8 s) and picture stimuli (30 s), we considered a tracking ratio of 47.17% to be satisfactory (see, for comparison, Gulz et al, 2020, in which preschoolers had an average tracking ratio of 50.4%, and LoBue et al, 2017, who used a tracking ratio cut‐off of 15% with 4‐ to 24‐month‐olds; average tracking ratio was not reported). We also note that the main findings of the study remained largely unchanged when infants with tracking ratios above and below the median are analyzed separately (see Supplemental Material 5) and that no correlations were found between tracking ratio and any main measures of the study.…”
Section: Methodsmentioning
confidence: 99%
“…The recent two years of educational AI lies on mobile platform, game-based learning or online analytics system on a computer machine, VR/AR or mixed reality (IJAIED, 2020). For examples, both the research of smartphone Python tutor (Fabic, Mitrovic and Neshatian, 2019) and Teachable Agent-based game with eye-tracking capabilities (Gulz, Londos, and Haake, 2020) showed that the AI are effective in enhancing learning and teaching. Limited literatures, nevertheless, are focused in educational humanoid robotics.…”
Section: Introductionmentioning
confidence: 99%